Irishness on the Margins Minority and Dissident Identities (New Directions in Irish and Irish American Literature, 2018)
This collection examines the presence of minority communities and dissident voices in Ireland both historically and in a contemporary framework. Accordingly, the contributions explore different facets of what we term "Irish minority and dissident identities," ranging from political agitators drowned out by mainstream narratives of nationhood, to identities differentiated from the majority in terms of ethnicity, religion, class and health; and sexual minorities that challenge heteronormative perspectives on marriage, contraception, abortion, and divorce. At a moment when transnational democracy and the rights of minorities seem to be at risk, a book of this nature seems more pressing than ever. In different ways, the essays gathered here remind us of the importance of 'rethinking' nationhood, by a process of denaturalisation of the supremacy of white heterosexual structures.